Analysis of the vibration caused by porting on the intake and exhaust channels of a 150 cc Kawasaki Ninja driver - Eko Saputra Eko Saputra; Subekti Subekti; Tulus Supriyanto (JTTM : Jurnal Terapan Teknik Mesin, 2023)
Motorcycle vehicles are very popular because they are easy to maneuver and fast, so they are the most popular in various aspects of transportation in urban areas. However, motorbike drivers get tired easily. Acute fatigue, fatigue, chronic sleepiness, sleep disturbances, and heavy workloads have been associated with reduced performance in psychomotor tests and driving simulators and increased rates of motor vehicle crashes, injuries and deaths in certain populations. One that must be considered is the spread of vibrations originating from the piston motor. This is due to vibrations occurring in the work environment and distributed to the body of the workforce or objects in the workplace or work environment throughout the body in the form of mechanical vibrations originating from machines or mechanical equipment. Therefore, the purpose of this study will be to determine the effect of port placement on the intake and exhaust channels on vibrations throughout the body (Whole Body Vibration). Tissue resonance throughout the human body causes health problems. The standard or threshold value for the whole body vibration level that applies at the international level refers to ISO 2631. The test results on the driver’s arm with a rotational speed of 9900 rpm at the standard obtained a frequency of 6 Hz and an amplitude of 0.911137 mm/s2, after porting, the frequency is 7 Hz and the amplitude is 0.771992 mm/s2. Meanwhile, on the driver’s feet with a rotational speed of 9900 rpm, the standard obtained a frequency of 3 Hz and an amplitude of 12.0214 mm/s2, after porting a frequency of 3 Hz and an amplitude of 18.6765 mm/s2 was obtained. The results of this study can be concluded that the use of ports on motorbikes will cause riders to experience fatigue more quickly than standard motorbikes. Because the average ported has a greater amplitude than the standard conditions